2006
DOI: 10.1002/jmv.20668
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant newcastle disease virus capsids displaying enterovirus 71 VP1 fragment induce a strong immune response in rabbits

Abstract: The complete VP1 protein of EV71 was truncated into six segments and fused to the C-terminal ends of full-length nucleocapsid protein (NPfl) and truncated NP (NPt; lacks 20% amino acid residues from its C-terminal end) of newcastle disease virus (NDV). Western blot analysis using anti-VP1 rabbit serum showed that the N-terminal region of the VP1 protein contains a major antigenic region. The recombinant proteins carrying the truncated VP1 protein, VP1(1-100), were expressed most efficiently in Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
4
27
0
1
Order By: Relevance
“…For EV71, investigation of T cell immunity has also mainly focused on VP1, and several HLA-class II-restricted T cell epitopes have been determined within this Ag (27,29). Moreover, a collection of studies demonstrate that VP1 is the dominant target of neutralizing Abs in EV71, and thus, VP1 has been broadly explored for subunit vaccine development, priming strong humoral immunity in a mouse model (15,52,53). However, compared with an N-terminal-biased neutralizing determinants distribution in humans, distribution of neutralizing Ab epitopes in mouse model reveals no N-or C-terminal bias, and numbers of epitopes are identified in the C-terminal of VP1 in mouse model (52,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…For EV71, investigation of T cell immunity has also mainly focused on VP1, and several HLA-class II-restricted T cell epitopes have been determined within this Ag (27,29). Moreover, a collection of studies demonstrate that VP1 is the dominant target of neutralizing Abs in EV71, and thus, VP1 has been broadly explored for subunit vaccine development, priming strong humoral immunity in a mouse model (15,52,53). However, compared with an N-terminal-biased neutralizing determinants distribution in humans, distribution of neutralizing Ab epitopes in mouse model reveals no N-or C-terminal bias, and numbers of epitopes are identified in the C-terminal of VP1 in mouse model (52,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Nt-VP1t and the control full length nucleocapsid protein of NDV (N) proteins were produced and purified as described previously (Sivasamugham et al, 2006). The proteins were quantitated by the Bradford assay, electrophoresed in a 12% SDS-PAGE gel and blotted onto a nitrocellulose membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, VP1 has become an ideal target for immunogenicity studies and vaccine development (Wu et al, 2001;Foo et al, 2007b). Recently, we showed that immunization with the first 100 amino acids of VP1 (VP1t) fused to a truncated nucleocapsid protein (Nt) of NDV, which served as a carrier molecule (Kho et al, 2001;Yusoff and Tan, 2001;Rabu et al, 2002), induced strong antibody responses in rabbits (Sivasamugham et al, 2006). This study showed that this recombinant protein, labeled as Nt-VP1t, may represent a useful candidate for EV71 vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…4). Considering residues that are located in previously predicted antigenic regions of the immunodominant VP1 capsid protein (Cello et al, 1993;Foo et al, 2007;Huang et al, 2009;Samuelson et al, 1994;Sivasamugham et al, 2006), B1-B5 viruses differed from genogroup C viruses at residue 164 and or 43. The B1* 9443 and B1 15051 isolates, which showed differences in antigenicity, differed from other genogroup B and C viruses, Fig.…”
Section: Amino Acid Sequence Comparisonmentioning
confidence: 99%